Emerging Bedaquiline Resistance in Pulmonary Tuberculosis Patients of a Tertiary Hospital in Jakarta, Indonesia - Fathiyah Isbaniah; Budi Haryanto; Nabila Assakinah Lubis; Cindy Refina Maharani; Heidy Agustin; Faiza Hatim; Riyadi Sutarto; Raden Rara Diah Handayani; Muhammad Nashirul Islam; Muhammad Hibban Heldian; Fathia Amalia Faizal; Aulia Rizkia Herawati (Jurnal Respirasi, 2026)
Introduction: Tuberculosis (TB) continues to pose significant health and economic challenges globally. Drug-resistant TB (DR-TB), particularly resistance to bedaquiline (BDQ), threatens the efficacy of current treatment regimens. Limited phenotypic drug susceptibility testing (DST) capacity exacerbates the issue, delaying appropriate interventions. This study examined BDQ resistance patterns among pulmonary DR-TB patients in Indonesia, where evidence on BDQ resistance remains scarce. Methods: A retrospective analysis of 393 DR-TB cases was conducted using data from the National TB Database (SITB) at Persahabatan National Respiratory Referral Hospital, Jakarta, Indonesia, between 2021 and 2023. Patients were classified based on the World Health Organization (WHO) 2022 DR-TB guidelines. Resistance patterns were determined through phenotypic DST using the BACTEC Mycobacteria Growth Indicator Tube (MGIT) system. Descriptive statistics summarized patient demographics and resistance profiles. Results: Among the 393 patients, 10 (2.54%) demonstrated BDQ resistance, with 8 cases arising without prior BDQ exposure. Mono/poly-resistance to Rifampicin and/or Isoniazid was the most prevalent pattern (44.29%). Multidrug-resistant TB (MDR-TB) was observed in 40.20% of cases, while pre-extensively DR and extensively DR-TB constituted 7.90% and 0.25%, respectively. Comorbidities, predominantly diabetes mellitus (DM), were identified in 33.59% of patients. Conclusion: This study revealed an alarming BDQ resistance rate (2.50% in MDR-TB cases), underscoring the urgent need for improved access to DST and TB management infrastructure in Indonesia. Strengthening diagnostic capacity and monitoring systems is critical to mitigating the spread of resistance and supporting effective treatment strategies.